2015
DOI: 10.1159/000374075
|View full text |Cite
|
Sign up to set email alerts
|

Baicalein Inhibits MMPs Expression via a MAPK-Dependent Mechanism in Chondrocytes

Abstract: Background: Baicalein is a flavonoid isolated from Scutellaria baicalensis Georgi. Here, we investigated the anti-osteoarthritic effect of baicalein in vitro and in vivo. Methods: Interleukin-1 beta (IL-1β)-induced chondrocytes were treated with different concentrations of baicalein, real-time PCR and ELISA were performed to detect the matrix metalloproteinases (MMPs) expression. Western blot was used to evaluate the mitogen-activated protein kinase (MAPK) expression. In experimental osteoarthritis (OA), rabbi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 28 publications
3
31
0
Order By: Relevance
“…These enzymes can cleave collagen II and aggrecan in cartilage. Thus, downregulation of these enzymes could be beneficial to cartilage [25, 26]. In this study, stimulation of IL-1β resulted in the increased expression of ADAMTS-5, ADAMTS-4, MMP-13, and MMP-1.…”
Section: Discussionmentioning
confidence: 81%
“…These enzymes can cleave collagen II and aggrecan in cartilage. Thus, downregulation of these enzymes could be beneficial to cartilage [25, 26]. In this study, stimulation of IL-1β resulted in the increased expression of ADAMTS-5, ADAMTS-4, MMP-13, and MMP-1.…”
Section: Discussionmentioning
confidence: 81%
“…However, it has been well established that miRNAs is involved in OA. Several miRNAs have been identified as having aberrant expression levels in osteoarthritis, such as miR-9, miR-27, miR-34a, miR-140, miR-146a, miR-558 and miR-602[7, 19, 24]. Increasing amounts of evidence have indicated that there is an existing link between miRNAs and osteoarthritis in the pathogenesis of OA.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, IL-1β promotes degradation of certain components of the cartilage extracellular matrix, such as type II collagen, and disrupts cartilage integrity [7]. Therefore, disrupting the activity of pro-inflammatory cytokines and subsequent MMP-13 expression has become an important strategy for reducing cartilage degradation in OA [8, 9]. …”
Section: Introductionmentioning
confidence: 99%